STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KEDISIPLINAN GURU PADA MAN 1 KABUPATEN ACEH UTARA - Muhammad Kautsar; Yusrizal Yusrizal; Bahrun Bahrun (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2020)
A school principal as a top manager has a strategic role in fostering the school teachers’ work discipline. The objective of his research was to describe the programs or policies made and the obstacles encountered by the principal in fostering the teachers’ work discipline at Islamic State Senior High School (MAN) 1 of Aceh Utara Regency. A descriptive – qualitative approach was used in conducting this research, and the data were collected by doing interviews, observation, and documentation. The research subjects were the school principal and the school teachers. The results indicate that the aim of the programs fostering the teachers’ work discipline was to achieve the learning goals which might expectedly lead to the improvement of the school quality. Each program was arranged to provide a good, effective, and fun learning which should be the school goals – oriented. It was also found that in facing the teachers with a moderate level of work commitment, the principal implemented situational leadership while in dealing with the teachers who had higher level of work commitment, the principal implemented consultative and participative leadership. In addition, the principal often discussed with the teachers and listen to their ideas. The obstacles encountered by the principal in fostering the teachers’ work discipline and motivation were several teachers who came late to the school, those who prepared the incomplete learning tools, and those who used no media in teaching and learning process. Abstrak Kepala sekolah sebagai top manager memiliki peran yang strategis dalam meningkatkan disiplin kerja guru. Penelitian ini bertujuan untuk mendeskripsikan program kepala sekolah, kebijakan kepala sekolah untuk meningkatkan komitmen kerja guru, serta kendala kepala sekolah dalam meningkatkan kedisiplinan guru pada MAN 1 Kabupaten Aceh Utara. Penelitian ini menggunakan pendekatan deskriptif kualitatif.Teknik pengumpulan data yang digunakan adalah wawancara, observasi, dan studi dokumentasi.Subjek penelitian kepala sekolah dan guru. Hasil penelitian menunjukkan bahwa program peningkatan disiplin kerja guru bersasaran untuk tercapainya proses pembelajaran dengan optimal, sehingga pada akhirnya mutu sekolah dapat ditingkatkan. Setiap penyusunan program diarahkan agar proses pembelajaran berjalan dengan baik, efektif, dan menyenangkan, dan berorientasi kepada pencapaian tujuan sekolah. Kebijakan kepala sekolah untuk meningkatkan komitmen guru dengan menerapkan kepemimpinan yang bersifat situasional bagi guru-guru yang komitmen kerjanya biasa, tetapi sikap mereka lebih patuh dalam melaksanakan tugasnya, kepala sekolah menerapkan kepemimpinan konsultatif dan partisipatif. Kepala sekolah banyak berdiskusi untuk mendapatkan cara yang disetujui oleh guru-guru. Kendala dalam meningkatkan disiplin kerja guru antara lain masih ada sebagian kecil guru yang datang terlambat ke sekolah, masih ada guru yang tidak menyiapkan perangkat pembelajaran dengan lengkap, tidak pernah menggunakan media dalam melaksanakan pembelajaran.